2017
DOI: 10.1038/s41467-017-00625-1
|View full text |Cite
|
Sign up to set email alerts
|

A secreted antibacterial neuropeptide shapes the microbiome of Hydra

Abstract: Colonization of body epithelial surfaces with a highly specific microbial community is a fundamental feature of all animals, yet the underlying mechanisms by which these communities are selected and maintained are not well understood. Here, we show that sensory and ganglion neurons in the ectodermal epithelium of the model organism hydra (a member of the animal phylum Cnidaria) secrete neuropeptides with antibacterial activity that may shape the microbiome on the body surface. In particular, a specific neurope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 49 publications
8
85
0
Order By: Relevance
“…A recent study of Augustin et al provided evidence supporting the first scenario, [37] and showed that some sensory and ganglion neurons express a cationic neuropeptide called NDA-1 ( Figure 3E and F), secrete it into the mucus layer and regulate the spatial distribution of the main colonizer, the Gram-negative bacterium Curvibacter, along the Hydra trunk. The density of Curvibacter colonization is relatively low in the foot and tentacles of Hydra, where NDA-1 is strongly expressed, compared to the body Figure 1.…”
Section: Hydra Neurons Shape the Microbiotamentioning
confidence: 80%
See 4 more Smart Citations
“…A recent study of Augustin et al provided evidence supporting the first scenario, [37] and showed that some sensory and ganglion neurons express a cationic neuropeptide called NDA-1 ( Figure 3E and F), secrete it into the mucus layer and regulate the spatial distribution of the main colonizer, the Gram-negative bacterium Curvibacter, along the Hydra trunk. The density of Curvibacter colonization is relatively low in the foot and tentacles of Hydra, where NDA-1 is strongly expressed, compared to the body Figure 1.…”
Section: Hydra Neurons Shape the Microbiotamentioning
confidence: 80%
“…All multicellular animals emerged in a world that was already densely populated by microbes, and all extant animals are multiorganismal and colonized by a large number of symbiotic microbes. [43,44] Our recent studies demonstrate the existence of such communication in non-bilaterian animals as well, [24,37] and suggest a universal role of the nervous system in mediating host-microbe interactions throughout the Metazoa. [4] The emergence and evolution of the nervous system must be also considered in the context of host-microbe interactions.…”
Section: Rethinking the Role Of The Nervous Systemmentioning
confidence: 87%
See 3 more Smart Citations